Selective Device for Separation of Shrimp and Fish in Trawls - N., Subramonia Pillai; M.D., Varghese; T., Joseph Mathai (Fishery Technology, 2025)
A new separator device with horizontally divided codend has been developed for segregation of shrimp and fish during shrimp trawling. The results of fishing trials carried out with the device indicated that about 90% of the shrimp was caught in the lower part of codend and fish was dominant (87%) in the upper part. The advantages of this device are also highlighted.